2011
DOI: 10.1080/87565641.2010.549876
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Findings: Neural Responses to Feedback Regarding Betrayal and Cooperation in Adolescent Anxiety Disorders

Abstract: This study examined patterns of neural response to feedback received during simulated interpersonal interactions in adolescents with anxiety disorders and healthy peers. To this aim, behavioral and neural responses during the Prisoner's Dilemma (PD) game, an economic exchange task, were compared between adolescents with anxiety disorders (N=12) and healthy controls (n=17). Participants were deceived to believe that their co-player (a pre-programmed computer algorithm) was another study participant. Anxious par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 73 publications
2
32
3
Order By: Relevance
“…The data further suggest that this association may be somewhat specific to features of depression, with no such effects seen for the anxiety or stress subscales of the DASS-21. Support for this interpretation can be seen in a recent study by the same researchers (McClure et al, 2011) who were unable to replicate this effect in a sample of exclusively anxious adolescents. This finding suggests an interesting avenue for future research into the dynamics of social behaviour among individuals with mood disorders.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The data further suggest that this association may be somewhat specific to features of depression, with no such effects seen for the anxiety or stress subscales of the DASS-21. Support for this interpretation can be seen in a recent study by the same researchers (McClure et al, 2011) who were unable to replicate this effect in a sample of exclusively anxious adolescents. This finding suggests an interesting avenue for future research into the dynamics of social behaviour among individuals with mood disorders.…”
Section: Discussionmentioning
confidence: 53%
“…First, in order to maximise ecological validity, participants were told that they were playing an online game with another participant, however, we did not include a manipulation check to assess whether this deception was successful. It should be noted, however, that this omission is shared by previous studies that have examined individual differences associated with performance on the IPD (e.g., Rilling et al, 2007), and there is evidence that participants do not systematically differ in game-play on the IPD as a function of whether they believe the deception (e.g., McClure et al, 2011). Second, in order to maximise statistical power a within-subjects design was used wherein each participant completed both conditions of the IPD task (standard condition followed by affective feedback condition).…”
Section: Discussionmentioning
confidence: 84%
“…The TPJ is involved in cognitive processes such as theory of mind and psychological perspective taking (Saxe and Kanwisher, 2003; Decety and Grezes, 2006) that play a fundamental role in human social interactive behavior. Hyperactivity has been noted in this region in anxious patients during negative social interactions (McClure-Tone et al, 2011) and altered function is considered a potential mechanism in disorders such as autism (Kana et al, 2012). Given that the TPJ is responsive to the emotional, social, and moral aspects (Kret et al, 2011; Koster-Hale et al, 2013) of stimuli involving social interaction, stress-related over-mentalizing during negative social interactions, mediated in part through the TPJ, may be a psychopathological mechanism amenable to treatment with AVPR1a antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these studies have demonstrated increased amygdala activity, [11,12] increased ventrolateral prefrontal cortex (VLPFC) activity, [12,13] and increased activity within the anterior cingulate cortex. [14] Specifically, in pediatric patients with GAD, dysfunction within the anterior limbic network (ALN), a collection of subcortical and cortical structures involved in the modulation and expression of complex affective states has frequently been noted. [12,[15][16][17][18] Functional magnetic resonance imaging (fMRI) studies, for instance, have demonstrated abnormal activation of the amygdala [12,17] and VLPFC, [12,13,16,19] and more recently, several studies have demonstrated altered functional connectivity among these structures.…”
Section: Introductionmentioning
confidence: 99%